2019
DOI: 10.1289/ehp3705
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Profiling before, during, and after the Beijing Olympics: A Panel Study of Within-Individual Differences during Periods of High and Low Air Pollution

Abstract: Background:The metabolome is a collection of exogenous chemicals and metabolites from cellular processes that may reflect the body’s response to environmental exposures. Studies of air pollution and metabolomics are limited.Objectives:To explore changes in the human metabolome before, during, and after the 2008 Beijing Olympics Games, when air pollution was high, low, and high, respectively.Methods:Serum samples were collected before, during, and after the Olympics from 26 participants in an existing panel stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 54 publications
5
23
0
5
Order By: Relevance
“…Metabolomics technology can be used to identify early health effects of heavy metals in PM and to reveal the underlying mechanisms, which has been applied in metabolic disturbance research associated with PM exposures ( Du et al, 2020 , Zhang et al, 2019 ). For example, a quasi-experiment during the Beijing Olympics showed significant differences in serum metabolites between high-exposure and low-exposure periods ( Mu et al, 2019 ). A crossover trial in Shanghai reported exposure to PM 2.5 was correlated with obvious changes in both serum and urine metabolites ( Li et al, 2017a , Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics technology can be used to identify early health effects of heavy metals in PM and to reveal the underlying mechanisms, which has been applied in metabolic disturbance research associated with PM exposures ( Du et al, 2020 , Zhang et al, 2019 ). For example, a quasi-experiment during the Beijing Olympics showed significant differences in serum metabolites between high-exposure and low-exposure periods ( Mu et al, 2019 ). A crossover trial in Shanghai reported exposure to PM 2.5 was correlated with obvious changes in both serum and urine metabolites ( Li et al, 2017a , Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The application of the bootstrapping approach to module stability to the metabolomics dataset from an air pollution study [28] demonstrates the utility of this approach for omics data, high‐dimensional data, and network analysis in general. Although the stability levels were in the low range, we were able to determine an appropriate threshold and modules that resulted in biologically meaningful modules.…”
Section: Discussionmentioning
confidence: 99%
“…The approach to bootstrapping stability was also applied to a high‐throughput metabolomics dataset. The data were collected from 26 participants at three‐time points, which were before, during and after, the 2008 Beijing Olympics [28]. During the Olympics, there were government‐mandated restrictions that aimed to reduce pollution levels and thus decreased exposure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations